A retrospective evaluation of zirconia-fixed partial dentures in general practices: An up to 13-year study. Issue 2 (February 2015) - Håff, Anna; Löf, Hanna; Gunne, Johan; Sjögren, Göran
Highlights: Ninety-four percent of the Y-TZP FPDs evaluated performed satisfactorily. The survival rate of the Y-TZP FPDs was within the same range as for metal–ceramic FPDs. For plaque and bleeding no significant differences were seen compared with the controls. Based on a visual analog scale patient satisfaction with the evaluated FPDs was high. Abstract: Objectives: To evaluate zirconia-based fixed partial dentures (FPDs) after more than 8 years in clinical service. Methods: Patients treated between 2000 and 2004 with zirconia FPDs were identified from the records of a manufacturer of FPD substructures. Of the 45 patients who met the inclusion criteria 30 attended the appointment and 33 FPDs were evaluated using modified California Dental Association (CDA) criteria. In addition, plaque and the bleeding index were registered. Patient satisfaction with the restorations was evaluated using a 10-point visual analog scale (VAS). Results: All the FPDs were made using CAD/CAM and hot isostatic pressed yttria-tetragonal zirconia polycrystal (HIPed Y-TZP) ceramic (Denzir) and were placed within general practices. The mean observation period was 9.6 ± 1.6 years (range 3.0–13.1 years). The CDA rating was 90% satisfactory for the surface. Corresponding figures for anatomic form, color and margin integrity were 94%, 100% and 94%, respectively. Regarding surface three (9.7%) FPDs exhibited veneer chipping and were rated 'not acceptable'. For margin integrity two (6.5%) were rated 'not acceptable' because of caries. For anatomic form two (6.1%) were rated 'not acceptable' due to two lost FPDs. No significant differences were seen between the FPDs and controls for plaque and bleeding. The Kaplan–Meier survival rate (still in clinical function) was 94%, the success rate (technical events accounted for) 91% and (biological events accounted for) 73%. Based on the VAS the mean value for patient satisfaction was 9.3 ± 1.2. Significance: Ninety-four percent of the FPDs were still in clinical function. HIPed Y-TZP could serve as an alternative for FPD treatments similar to those in the current study.